POLITICAL PROCESSES IN RUSSIA AND ISLAMIC RADICALISM - GALIULLINA, Svetlana; SULEYMANOV, Artur; NIYAZOVA, Gulsina; BAKULINA, Yulia (CENTRAL ASIA AND THE CAUCASUS, 2017)
The authors discuss the significant role Islamic radicalism plays in shaping political processes in Russia, highlighting its global and internal sources. They argue that Islamic radicalism has evolved from a potential threat to an active risk to Russia's national security, making the study of its impact on the Russian political agenda critical. The latest methodological tools allow for deeper analysis of this complex phenomenon and help forecast its spread at regional and local levels, especially under globalization's influence.Islamic radicalism is characterized as a new social and political phenomenon, transcending its origins as a “confessional issue” and presenting a global threat, as evidenced by recent violent actions by Islamist radicals that have incited Islamophobia worldwide. The authors note that political conflicts stemming from religious differences have gained prominence, affecting social and political spheres. They stress the danger of radical Islamist teachings, which can undermine the social and political order of states.Importantly, the authors differentiate between "Islamic radicalism" and "Islamic extremism." While both concepts are similar, they are not identical. Islamic radicalism encompasses the formation of political views and a fundamentalist worldview, which can exist without leading to criminal acts. In contrast, Islamic extremism refers to the active application of radical ideologies through means such as terrorism, inciting religious conflicts, and attempts to seize political power. The authors pose the question of whether these two phenomena are interconnected.